STRATEGI GURU PAI DALAM MEMBANGUN MOTIVASI BELAJAR SISWA - Rahimah, Siti; Rohana, Siti (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
PAI teachers have the responsibility to not only teach religious material but also motivate students to be more enthusiastic in learning. an energetic taeacher is needed in the teaching and learning process so that it can run well. energetic teachers are also important in achieving student learning outcomes. This study aims to determine teacher creativity in an effort to increase student learning motivation. This research is a descriptive qualitative study whose data collection is obtained by means of observation, interviews and documentation. From the results of this study, the author can conclude that a teacher's energy in increasing student learning motivation is effective in increasing student learning motivation atthis is evidenced by the increase in student learning outcomes at the end of the semester by getting scores above the average and the results of competition championship achievements. Other evidence can be seen from the activeness of students when participating in the teaching and learning process despite the lack of school facilities. Keywords: Islamic Religious Education Teacher, Learning motivation